2008
DOI: 10.4103/0972-2327.42938
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis presenting as Parkinsonism

Abstract: Cirrhosis presenting as Parkinsonism is a distinct subset of acquired chronic hepatocerebral degeneration. The entity is not rare, and unless suspected, cirrhosis can easily be overlooked. We report our experience with three such patients. They presented to us, over a period of two years, with symmetrical Parkinsonism and were later diagnosed to have cirrhosis with portal hypertension. All patients had minimal or absent tremors. Reversal of serum albumin to globulin ratio and evidence of cirrhosis on abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The symptoms include hypermanganesemia, polycythemia, dystonia, chronic hepatic disease, cirrhosis, motor neuropathy, and behavioral disturbances with differing severity (70). These symptoms have a large overlap with patients with PD; some studies have even found an increased occurrence of Parkinsonism with sufferers of cirrhosis (up to 21%) (35, 201). Consistent with this idea, patients presenting with Parkinsonian symptoms who have decreased ability to excrete biliary Mn 2+ suffer from Mn 2+ -induced neurotoxicity (1, 35).…”
Section: Manganese Neuronal Healthmentioning
confidence: 99%
“…The symptoms include hypermanganesemia, polycythemia, dystonia, chronic hepatic disease, cirrhosis, motor neuropathy, and behavioral disturbances with differing severity (70). These symptoms have a large overlap with patients with PD; some studies have even found an increased occurrence of Parkinsonism with sufferers of cirrhosis (up to 21%) (35, 201). Consistent with this idea, patients presenting with Parkinsonian symptoms who have decreased ability to excrete biliary Mn 2+ suffer from Mn 2+ -induced neurotoxicity (1, 35).…”
Section: Manganese Neuronal Healthmentioning
confidence: 99%
“…In a case report by Noone et al ., two patients who presented with slowly progressive Parkinsonism were subsequently diagnosed to have cirrhosis based on subtle abnormalities in liver function tests and MRI findings. [ 5 ] In all reports of Parkinsonism in liver disease, except one, Parkinsonism was slowly progressive. In a case report by Pendlebury et al ., a similar stroke-like presentation with dysarthria, dysphagia and difficulty in walking was reported in a 17-year-old boy who was subsequently diagnosed to have Wilson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with poor survival and a high recurrence rate unless the underlying cause is successfully treated (Vilstrup et al, 2014). In a middle-aged patient with a rapid onset of symmetric Parkinsonism, hepato-cerebral Parkinsonism should be suspected (Noone et al, 2008). In the literature, the reported prevalence rate ranges from as low as 3.5 -4.2% to as high as 21.6% (Burkhard et al, 2003;Tryc et al, 2013;Kang et al, 2011).…”
Section: Case Presentationmentioning
confidence: 99%
“…In the literature, the reported prevalence rate ranges from as low as 3.5 -4.2% to as high as 21.6% (Burkhard et al, 2003;Tryc et al, 2013;Kang et al, 2011). Global hypokinesia and gait impairment are early Parkinsonian symptoms in cirrhosis, whereas dementia and resting tremors are uncommon symptoms (Noone et al, 2008).…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation

Parkinson’s mimicker in Acute and Chronic Hepatic Encephalopathy

Mohamad Shahrunizam Awang Setia,
Mohamad Izzat Arslan Che Ros,
Nurul Hafidzah Rahim
et al. 2023
BJMS